A cost-effective approach to reducing carbon deposition and resulting deactivation of oxygen carriers for improvement of energy efficiency and CO2 capture during methane chemical-looping combustion. (1st May 2017) - Huang, Xin; Wang, Xingjun; Fan, Maohong; Wang, Yonggang; Adidharma, Hertanto; Gasem, Khaled A.M.; Radosz, Maciej
Graphical abstract: Highlights: The carbon deposition highly related to the dispersion of metal oxide on support. Steam could avoid the carbon deposition, improve the fuel efficiency to ∼100%. Steam could preserve the pore structure of OCs from damage during the multicycles. Steam could strengthen the redistribution of CuO on Al2 O3 surface at 800 °C. Abstract: The objective of this research is to investigate the effect of steam on reducing carbon deposition during CH4 chemical looping combustion (CLC) on a fixed bed reactor. Steam proved to be significantly effective not only for the fuel utilization efficiency of CLC but also for the stability of the oxygen carrier (OC). The evaluation tests were performed with CuO/γ-Al2 O3 OCs prepared with three different methods. The results showed that OC prepared using co-precipitation method performed the best with the highest reactivity for CH4 combustion at low temperature (700 °C) compared to that prepared using mechanical mixture and impregnation methods. It was also found that the carbon deposition was the main reason for the low combustion efficiency and the deactivation of OCs in redox cycles. For OCs at 800 °C, after 10 cycles without steam, 25–44% CO2 selectivity reductions were observed, accompanied by Barrett-Joyner-Halenda (BJH) pore volume decreases of 31–47%. With the steam introduction, the CO2 selectivity consistently achieved ∼100% in 10-cycle CLC, and the pore volumes of OCs decreased by only 11–22%, which was mostly attributed to the carbon-steam gasification reaction. The OCs for CH4 CLC with and without steam were characterized by using different methods, including surface area and pore analysis, thermal gravimetric analysis (TGA), X-ray diffraction (XRD), H2 temperature programming reduction (TPR), and scanning electron microscope (SEM). The results demonstrated that steam could easily gasify the carbon deposition, greatly intensify the redox degree of OCs at 800 °C, and strengthen the redistribution of Cu on the surface of Al2 O3, contributing to the fine and uniform distribution of CuO. Therefore, steam can be successfully used for considerable enhancement of the overall performance of CH4 CLC.